2013
DOI: 10.5539/ies.v6n7p119
|View full text |Cite
|
Sign up to set email alerts
|

Pros and Cons of Using ICT in Teaching ESL Reading and Writing

Abstract: Information and Communication Technologies (ICTs) play a major role in creating a new and improved model of teaching and learning. A great number of studies have been conducted to examine the advantages of integrating ICT in language education in general and English as a Second Language (ESL) teaching and learning in particular. However, there is a need for more studies on the disadvantages of using ICT in language education. This study aims to identify both advantages and disadvantages of using ICT in teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 17 publications
3
64
0
3
Order By: Relevance
“…A response to a follow-up interview question showed that all students use social media out of their liberty, to enhance the learning process. This study did not extract data from academic administrators; however, the literature suggests that initiatives from instructors or institution management would add value to the use of social platforms for learning (Ni 2013;Yunus et al 2013). This is because students will have the obligation to use the platform to access learning materials and make their discussions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A response to a follow-up interview question showed that all students use social media out of their liberty, to enhance the learning process. This study did not extract data from academic administrators; however, the literature suggests that initiatives from instructors or institution management would add value to the use of social platforms for learning (Ni 2013;Yunus et al 2013). This is because students will have the obligation to use the platform to access learning materials and make their discussions.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the possible reasons include the lack of technical knowledge, teaching materials and other negative moral and social impacts that come with the traditional use of social media (Yunus et al 2013). Morally, parents and educators are concerned about possible negative impacts of using online social media in the learning process, which include exposure to pornography and cyber bullying (Tedla 2012).…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…Learners are more independent in fostering their own learning, especially when they are motivated and have interest in the learning process, which can be aroused using ICT (Yunus et al, 2013). It can be said that motivation plays a vital role in the success of a learner in ESL learning.…”
Section: 7discussionmentioning
confidence: 99%
“…The teaching of grammar should be fun to provide learners with better performance. As further supported by Yunus, Nordin, Salehi, Sun and Embi (2013), learners are able to improve their vocabulary acquisition through ICT.…”
Section: 2grammar In Esl Learningmentioning
confidence: 99%
“…Teachers should become knowledgeable in operating and managing the big umbrella of the new technological tools (Negoescu & Boștină-Bratu, 2016), from among which we need to mention: interactive whiteboards, computer, tablets, internet, videogames, smart phones, software programs for language learning, Skype messenger, blogging, television, social networks, projector, YouTube, Power Point, etc. In short, we advocate the use of ICT as a powerful tool for improving the effectiveness of foreign language teaching and learning at all levels, within the classroom didactic activities, as well as in non-educational environment (Yunus et al, 2013).…”
Section: The Advantages Of Using Ict In Foreign Language Teaching In mentioning
confidence: 99%